The Financial Impact of a Change in Thailand's Visa Regulations for Chinese Visitors - BI, Chuanchen; YANG, Wei (Journal of Posthumanism, 2025)
International tourism is significantly impacted by global political, financial, and environmental events. In Thailand, where tourism is a key economic driver, visa regulations play a crucial role in shaping travel demand. This study examines the financial impact of Thailand’s visa policies on Chinese visitors, focusing on the effects of the Beijing 2008 Olympic Games and the COVID-19 pandemic. Using a combination of econometric modeling and Computable General Equilibrium (CGE) analysis, the study evaluates changes in tourism revenue, visitor arrivals, and economic welfare. Findings indicate that visa restrictions during both events contributed to substantial financial losses, outweighing the potential economic benefits. Policymakers must balance security concerns with the economic consequences of restrictive visa policies. The study provides insights into how major events influence travel behavior and offers recommendations for sustainable tourism policies that minimize financial disruptions while ensuring long-term growth.